STUDY ON THE FACTORS THAT INFLUENCE THE FORMATION OF PRICES OF GOODS AND SERVICES - da Cruz, Allan Cardoso; Monteiro, Jamir Mendes (Revista Interface Tecnológica, 2023)
The formation of prices of goods and services is a relevant theme for understanding the economic changes in the market, as several factors directly influence the alteration of the purchasing value of material goods and consumer items. In this sense, this article aims to analyze and discuss the main factors that influence price formation in an economy, through a bibliographic and exploratory approach. From the literature review, factors such as the high dollar, seasonality, exclusivity, demand, and regulatory actions in the market were identified as the main indicators of the formation of prices of goods and services in the economy. Therefore, understanding these factors becomes essential for decision-making by managers and investors, as well as for critical analysis of government policies related to the market.